A hypoplastic model for pre- and post-liquefaction analysis of sands (2024)
This article proposes an extended constitutive model for liquefaction analysis of sands. The proposed model is formulated based on the hypoplastic model for granular soils by von Wolffersdorf (1996), enhanced with Intergranular Strain Anisotropy by Fuentes et al. (2019), which is usually referred to as ISA-hypoplasticity. The proposed extended model includes some modifications that are indispensable for the correct prediction of liquefaction-related analysis: (i) a new Lode-angle-dependent function for post-liquefaction shear strain accumulation, (ii) a modification for fabric change effects, (iii) the theory of the so-called semifluidized state. The first modification allows the model to predict shear strain accumulation in extension and compression during cyclic mobility. The second and third modifications, were initially developed by Liao et al. (2022) for hypoplasticity with conventional intergranular strain based on the pioneer work by Barrero et al. (2020) for Sanisand, and enable the model to reproduce fabric change effects upon loading reversal, and stiffness and dilatancy degradation at low effective stress levels, respectively. With the consideration of the new Lode-angle function, the proposed model realistically predict the increasing shear strain accumulation in both extension and compression without adopting a circular critical state surface, as adopted in Liao et al. (2022). The proposed model was carefully calibrated and validated based on a series of monotonic and cyclic triaxial tests on Zbraslav and Karlsruhe fine sands, considering various testing conditions. The comparison between experimental measurements and numerical predictions of undrained cyclic tests suggests that the proposed model accurately describes the pre- and post-liquefaction stages, as well as the stress attractors.